HUBUNGAN ANTARA KELINCAHAN DENGAN KETERAMPILAN DRIBBLING PADA CLUB SEPAKBOLA GEMPA FC KECAMATAN PANGEAN KABUPATEN KUANTAN SINGINGGI - Randa, Gusti; Agust, Kristi; ', Saripin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to determine whether there is a relationship the between Agility With Dribbling Skills on team Football club gempa Fc. Pangean districts Kuantan Singingi. The Forms of this research is a correlation study, the population in this study is the club Gempa Fc Pangean districts Kuantan Singingi, and the sample in this study is the club Gempa Fc. Pangean districts Kuantan Singingi numbered 18 people. In the Calculation of the correlation analysis of X and Y, where r tab at significant level α (0,05) = 0.639 means r arithmetic (0.639) > r tab (0,482), which means that the hypothesis is accepted and there is a meaningful relationship the between agility with dribbling skills on the club Gempa Fc. Pangean districts Kuantan Singingi, then it can be concluded that the relationship between the (X) premises Y or agility relationship with dribbling skills Football club Gempa Fc. districts Pangean Kuantan Singingi is significant Thus the dribbling skills Football club Gempa Fc. Pangean districts Kuantan Singingi predicted by their agelity.Keywords:, agility and dribbling skills